2020
DOI: 10.15766/mep_2374-8265.10973
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Advance Care Planning Communication: An Interactive Workshop With Role-Play for Students and Primary Care Clinicians

Abstract: Introduction: Increased clinician training on advance care planning (ACP) is needed. Common barriers to ACP include perceived lack of confidence, skills, and knowledge necessary to engage in these discussions. Furthermore, many clinicians feel inadequately trained in prognostication. Evidence exists that multimodality curricula are effective in teaching ACP and can be simultaneously targeted to trainees and practicing clinicians with success. Methods: We developed a 3-hour workshop incorporating lecture, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…To address this, research from this study highlighted the importance of ACP discussion among communities, where healthcare professionals are allowed to have sufficient time for ACP discussions with patients and families in a tranquil atmosphere. Previous studies published before the COVID‐19 pandemic suggested that equipping older patients, families and community‐based organizations with fundamental knowledge about ACP would promote awareness and support for person‐centered care for older people living in the community and their family caregivers 39–44 . The results of this study also identified facilitators for implementation of community‐based ACP during the COVID‐19 era: updating and disseminating scientific information on the regional pandemic situation.…”
Section: Discussionmentioning
confidence: 62%
“…To address this, research from this study highlighted the importance of ACP discussion among communities, where healthcare professionals are allowed to have sufficient time for ACP discussions with patients and families in a tranquil atmosphere. Previous studies published before the COVID‐19 pandemic suggested that equipping older patients, families and community‐based organizations with fundamental knowledge about ACP would promote awareness and support for person‐centered care for older people living in the community and their family caregivers 39–44 . The results of this study also identified facilitators for implementation of community‐based ACP during the COVID‐19 era: updating and disseminating scientific information on the regional pandemic situation.…”
Section: Discussionmentioning
confidence: 62%
“…Training should support doctors' knowledge and con dence in understanding relevant law and the civil and criminal consequences of not doing so. Short interactive education programs and workshops have been demonstrated to improve student and doctors knowledge and con dence in engaging in ACP, and their performance in simulated ACP activities (24,25). Prioritising the use of available training in end-of-life law by JMOs, as well as ongoing training to further support skill development, is critical to improving the provision of high-quality patient-focused care.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the population, most studies were carried out with healthcare professionals (physicians, nursing professionals, pharmacists, social service personnel, and ethicists) (n ¼ 16, 47%) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and undergraduate medical and nursing students (n ¼ 12, 35%). [31][32][33][34][35][36][37][38][39][40][41][42] The remaining studies (n ¼ 6, 18%) were carried out with healthcare students and professionals simultaneously, 7,[43][44][45] with volunteers 46 or with patients suffering from serious diseases and their caregivers. 47 Regarding effectiveness, the roleplay strategy was considered effective in all experimental or quasi-experimental studies in which it was used independently.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…16,17,25,28,34,40,41 In 12 studies (35%) it was only mentioned that roleplay was carried out by professors, clinicians, and/or researchers without specifying whether they had received any specific training for this purpose. 7,18,23,24,27,30,35,38,42,43,45,46 In one of the studies (4%), the roleplay strategy was carried out in partnership with a professional theater company. 44 In the remaining articles (n ¼ 14, 41%) no information was presented on who had carried out the roleplay activities.…”
Section: Studies Characteristicsmentioning
confidence: 99%